Цифрова компетентність вчителів закладів загальної середньої освіти: розвиток в умовах кризових трансформацій - Татарчук, Андрій, Тетяна Равлюк (My University, 2025)
The article is devoted to analyzing the dynamics of the development of digital competence among teaching staff and the general secondary education system of Ukraine under crisis conditions during 2021–2023. The study covers the period from COVID-19 adaptation to the full-scale invasion, which became a catalyst for accelerated yet uneven transformations. The methodological basis of the research is the analysis of data from two large-scale national studies conducted by the State Service of Education Quality of Ukraine in 2021 and 2022/2023. The results revealed two key stages in the dynamics of digital competence. At the first stage (2021, COVID-19 adaptation), there was a rapid instrumental mastering of digital tools, reflected in high levels of activity: 81% of teachers conducted online lessons, while 89.2% of school leaders and 81% of teachers maintained regular feedback. This indicated strong motivation and the ability for swift adaptation in the communicative and basic instrumental domains of digital competence. However, this stage was characterized by challenges related to insufficient experience in using specialized platforms and technical tools. At the second stage (2022/2023, wartime challenges), the education system demonstrated significant progress in the organizational dimension of digital competence and overall resilience. The transformation of learning formats — with blended and distance learning becoming dominant — required resource unification. As a result, 61% of school leaders implemented a unified educational platform, reducing the number of institutions without any platform use to only 1–5%. At the same time, in 2022/2023 new systemic challenges emerged due to martial law: 75% of teachers identified power outages and internet access problems as key obstacles. A persistent systemic issue throughout the crisis period was the methodological deficit of digital competence. It manifested in limited flexibility of planning and passive content use — no more than one-third of teachers engaged students in interactive activities, relying mostly on presentations and independent work. The dynamics of digital competence during the crisis period of 2021–2023 demonstrate successful and accelerated instrumental and organizational adaptation of teachers within the general secondary education system.
Keywords: dynamics of teachers’ digital competence, crisis conditions, distance learning, organizational competence, digital tools